Komunitas Biota Makrobentik di Perairan Pulau Ternate Maluku Utara - WD. Syarni Tala; Abdu Mas’ud; Ningsi Saibi (Jurnal Biologi dan Pembelajarannya (JB&P), 2025)
Ternate Island waters have high marine biodiversity, including macrobenthic biota. These biota are important components in the food web of aquatic ecosystems, bioturbators of aquatic sediments, and decomposers of organic materials. Macrobenthic biota can also be an indicator of the ecological quality of waters. This study aims to determine the species of macrobenthic biota, community structure including abundance, diversity, evenness, and dominance, as well as environmental factors that affect macrobenthic biota communities in the waters of Ternate Island, North Maluku. This research was conducted in the waters of Tabanga Beach and Kastela Beach, Ternate, North Maluku in March - June 2024. This research is a quantitative research. Sampling of macrobenthic biota using the transect-quadrat method. The results showed that the macrobenthic biota community in the waters of Ternate Island consisted of 85 species, 61 species were found in Tabanga Beach, 29 species were found in Kastela Beach, and 5 species were found in both beaches. Tenguella granulata has the highest abundance in Tabanga Beach and Echinometra mathaei has the highest abundance in Kastela Beach. Tabanga Beach has a high diversity value (H' = 3.39), while Kastela Beach is in the medium category (H' = 2.69). Macrobenthic biota community in these two waters have high evenness and there is no dominating species in the community. The results of macrobenthic biota community analysis in Ternate Island waters indicate that these waters are suitable for macrobenthic biota life.